Sigmatropic rearrangement of vinyl aziridines: expedient synthesis of cyclic sulfoximines from chiral sulfinimines - Moragas, Toni; Liffey, Ryan M.; Regentova, Dominika; Ward, Jon-Paul; Dutton, Justine; Lewis, William; Churcher, Ian; Walton, Lesley; Souto, J.A.; Stockman, Robert A. (Wiley-VCH Verlag, 2016)
A novel rearrangement of 2-vinyl aziridine 2-carboxylates to unusual chiral cyclic sulfoximines is described herein. The method allows the synthesis of substituted cyclic sulfoximines in high yields with complete stereocontrol, displaying a wide substrate scope under mild conditions. Further development of a one-pot process directly from sulfinimines shows the synthetic applicability of this protocol, providing access to complex chiral sulfoximines in only two steps from commercially available aldehydes. A mechanistic hypothesis and synthetic application in the formal synthesis of trachelanthamidine by transformation of a cyclic sulfoximine into a pyrroline is also disclosed.